0578 Self-reported Sleep Quality And Daytime Sleepiness In Obstructive Sleep Apnea Patients: The Role Of Depressive Symptoms. (27th April 2018) - Dubrovsky, B; Weingarten, J A; Cunningham, J; Abdelrahman, M; DeMilt, N; Ferreira, A; Inamac, A
Abstract: Introduction: Self-report measures of sleep and daytime sleepiness, including Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI) and Epworth Sleepiness Scale (ESS), are used to evaluate OSA patients. However, OSA has been associated with depression, and self-report sleep measures have been shown to relate to symptoms of depression in non-clinical samples and in OSA patients. We aimed to determine relative contributions of PSG variables and depressive symptomatology to PSQI, ISI and ESS in patients undergoing OSA evaluation. Methods: On the evening of PSG, 107 patients (18-89y.o., 64 women, 70 minorities) completed PSQI (normal range: PSQI<6), ISI (normal range: ISI<8), ESS (normal range: ESS<9), and Center for Epidemiologic Studies Depression Scale-Revised (normal range: CESDR<16). PSQI, ISI and ESS scores were hierarchically regressed on age, sex, BMI in the 1st step, and on total sleep time, sleep stage percentages, sleep latency, sleep efficiency, WASO, awakenings, arousal index, REM latency, AHI, SpO2% nadir, time spent below SpO2 90%, desaturation index, time above ETCO2 50mmHg, CESDR and CESDR-by-OSA(AHI≥5) interaction in the 2nd step, using step-wise entry. Results: Group means: AHI=12.5 ± 20.8 (61 patients had OSA, AHI≥5); PSQI=9.0 ± 3.9; ISI=11.8 ± 6.6; ESS=7.5 ± 4.6, CESDR=14.6 ± 11.9. Higher PSQI was related to lower N2% (p=0.001, R 2 =7%), lower N1% (p=0.003, R 2 =6%), and higher CESDR (p<0.001, R 2 =26%). Higher ISI was related to higher REM% (p=0.002, R 2 =6%) and higher CESDR (p<0.001, R 2 =34%). Higher ESS was related to higher sleep efficiency (p=0.007, R 2 =7%) and higher CESDR (p<0.001, R 2 =18%). CESDR was marginally elevated in patients with OSA (17.2 ± 12.3 vs. 12.9 ± 11.4, t=1.9, p=0.07). The CESDR-by-OSA interaction terms were not significant. Conclusion: Elevated depressive symptomatology plays a significant role in subjective sleep disturbance and daytime sleepiness, accounting for 18–34% of the variance in self-report sleep measures, similarly in patients with and without the OSA diagnosis. The OSA diagnosis was associated with only a marginal elevation of depressive symptoms. Support (If Any): None.